Elinor Ostrom: From Nepal Perspective - Pradhan, Prachanda (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
No abstract available DOI: http://dx.doi.org/10.3126/hn.v11i0.7168 Hydro Nepal Vol.11 2011 pp.69